Quality of Service to the Regional Road Transport Service - E.Shpuza, Suela (European Journal of Multidisciplinary Studies, 2016)
Performance is measured and done, the quality represents a key element to achieve the performance, especially customer service quality. In response to the pressure of globalization, the market increasingly competitive and volatile market dynamics that, many organizations actively seeking ways to add value to their services and improve their quality of service. Organizations usually tend to make their operations efficient priority. This process begins with the assessment of nevojave customers, their requirements and assessing the performance of domestic human resources in organization and performance depends on the outcome of the estimated earlier. Since this process can proceed in different directions. The causes of these results may be the lack of information and support of high-level management, performance standards unclear, inaccuracies assessors, very large number of forms to be completed and the use of software for the opposite purpose.